Clinical predictive score of intracranial hemorrhage in mild traumatic brain injury - Chaiyaporn Yuksen (2019)
© 2018 Yuksen et al. Background: Mild traumatic brain injury (TBI) is a common condition at the Emergency Medicine Department. Head computer tomography (CT) scans in mild TBI patients must be properly justified in order to avoid unnecessary exposure to X-rays and to reduce the hospital/transfer costs. This study aimed to evaluate which clinical factors are associated with intracranial hemorrhage in Asian population and to develop a user-friendly predictive model. Methods: The study was conducted retrospectively at the Emergency Medicine Department in Ramathibodi Hospital, a university-affiliated super tertiary care hospital in Bangkok, Thailand. The study period was between September 2013 and August 2016. The inclusion criteria were age >15 years and having received a head CT scan after presenting with mild TBI. Those patients with mild TBI and no symptoms/deterioration after 24 h of clinical observation were excluded. The predictive model and prediction score for intracranial hemorrhage was developed by multivariate logistic regression analysis. Results: During the study period, there were 708 patients who met the study criteria. Of those, 100 patients (14.12%) had positive head CT scan results. There were seven independent factors that were predictive of intracranial hemorrhage. The clinical risk scores to predict intracranial hemorrhage are developed with an accuracy of 92%. The score of >3 had the likelihood of intracranial hemorrhage by 1.47 times. Conclusion: Clinical predictive score of >3 was associated with intracranial hemorrhage in mild TBI.